Problems of land relations in electricity transmission - Baidabekov, Ауез; Zhumabaev A.A., Жумабаев А.А.; Kusebaev, Уалихан; Borgekova K.B., Боргекова К.Б. (Рroblems of engineering and professional education, 2023)
This article discusses issues related to the allocation of a land corridor along an overhead power line in the form of a sanitary protection and security zone and ensuring the environmental safety of the population